Analysis Of Students’ Errors Through Newman’s Theory In Addressing Critical Thinking Ability Questions As Examined Through Cognitive Style - Lupita, Lita; Meiliasari, Meiliasari; Hakim, Lukman El (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Mistakes frequently occur among students when interpreting mathematical problems or engaging with math exercises. This has contributed to the low PISA results in 2022, particularly reflected in a decline in mathematical proficiency, with Indonesia's average score decreasing by 1-3 points compared to previous assessments. Consequently, there is a pressing need to investigate the errors committed by students. This study aims to identify student errors through the lens of Newman's theory while addressing critical thinking ability questions in relation to cognitive style. The research design is descriptive qualitative, as it elucidates the mistakes made by students. The subjects of this study comprised 27 out of 84 seventh-grade students from SMP Negeri 139 Jakarta, who exhibited errors in responding to critical thinking ability questions involving combined material on flat-sided geometric shapes. The findings and conclusions of this study reveal that students with a Field Dependent (FD) cognitive style and those with a Field Independent (FI) cognitive style encounter reading errors, understanding errors, process skill errors, and coding errors; however, students with an FI cognitive style tend to make fewer mistakes than their FD counterparts.